(untitled) (Asian Journal of Medical and Biological Research, 2015)
An experiment was conducted to evaluate the effect of diets varying in protein concentrations on indigenous (desi) growing chicks reared under confinement system. The feeding trial was conducted with 144 indigenous female (desi) growing chicks during 12-22 weeks of age. The birds were divided into four dietary treatments each of three replications and reared on littered floor in an open-sided house. The number of birds in each replication was 12. Four iso-nitrogenous grower diets differing in protein contents were formulated to constitute dietary treatments. Diets for comparison were: control (a mixture of broken rice, rice polish, protein concentrate etc); low protein density (LPD): CP 15%; moderate protein density (MPD): CP 17% and high protein density (HPD): CP 19%. Metabolizable energy was maintained 2700 kcal/kg in every diet. The contents of CP, ME, calcium (Ca) and total phosphorous in MPD diet were fitted with the requirements calculated on the basis of BIS (Bureau of Indian Standard). Diets were formulated using locally available feedstuffs. Body weight and feed intake of the birds were recorded weekly. The results indicated that body weight and weight gain increased significantly in birds that received MPD diets in comparison with those received the other diets. Feed conversion ratio decreased significantly in all protein diets in comparison with the control. It is concluded indigenous (desi) female chicks may achieve up to 1.1kg body weight at 22 weeks of age when 17% CP is fed in a2700 kcal ME/kg diet. Asian J. Med. Biol. Res. June 2015, 1(1): 109-113